ONOMATOPE BAHASA DEVAYAN - Rika Kustina (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2020)
Onomatopoeia is the naming of objects or deeds by sound imitation. Imitation of sound does not only include animal, human, natural, or audible sounds, but also sounds that describe moving objects, collisions, or human feelings or emotions. In this study, onomatopoeia is the result of an imitation of sound (which is more or less the same as the original sound) and is arbitrary. This study aims to describe the Devayan language onomatopoeia of natural sounds, animal sounds and human voices. This type of research uses a qualitative descriptive approach. The data source of this research is 7 community leaders of Simeulue, namely native speakers of the Devayan language in Simeulue Cut, data obtained from sounds imitated by the community. Data collection techniques used in this study were interview, record, see and note technique. The results showed that imitations of sounds originating from natural sounds were found to be around 26 imitations of sounds, including imitations of the sound